Efektivitas Festival Anak dalam Meningkatkan Kreatifitas Siswa Nilai Kebersamaan dan Kepedulian Sosial dalam Tradisi Gotong Royong di Desa Buluh - Afriani Harahap; Putri Mayasari Perangin Angin; Elva Firanti Triananta; Indah Geana; Nurhayani Nurhayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the values of togetherness and social concern embedded in the gotong royong (mutual cooperation) tradition in Buluh Duri Village, Sipispis District, Serdang Bedagai Regency. Employing an ethnographic qualitative approach, the research examines the social meanings, patterns of interaction, and transformation of local values within the context of ongoing social change. Data were collected through participant observation, in-depth interviews with community leaders, local officials, and residents, as well as documentation of gotong royong activities in Gunung Pamela. The findings reveal that gotong royong functions as a mechanism of social value reproduction that fosters communal solidarity, collective responsibility, and emotional cohesion among villagers. Togetherness is reflected in collective labor and deliberation practices that reinforce community identity, while social concern manifests through altruistic acts of mutual assistance. Despite modernization and shifting participation patterns, the moral essence of gotong royong endures as both a cultural identity and a form of social capital. The study emphasizes the importance of revitalizing gotong royong values in development policies and character education to strengthen the social resilience of rural communities in Indonesia.